Traditions And Religious Relations: Perceptions Of Religious Group In Kerinci, Jambi - Wahyuni, Tela; Arafik, Valezza Juliani (Institut Agama Islam Negeri Kerinci, 2022)
Indonesia has many kinds of traditions. Each region in Indonesia has different habits, characteristics, and uniqueness, as well as the practices belonging to Kerinci Regency, Jambi Province, namely